2014
DOI: 10.1016/j.ypmed.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the challenges of conducting physical activity and built environment research in Latin America: IPEN Latin America

Abstract: Objective There is evidence linking the built environment (BE) with physical activity (PA), but few studies have been conducted in Latin America (LA). State-of-the-art methods and protocols have been designed in and applied in high-income countries (HIC). In this paper we identify key challenges and potential solutions to conducting high quality PA and BE research in LA. Methods The experience of implementing the IPEN data collection protocol (IPEN: International Physical Activity Environment Network) in Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 36 publications
4
117
1
8
Order By: Relevance
“…38,39 Specifically, in LMIC where car availability remains relatively low in comparison with HIC, AST may be more reflective of need rather than choice since a significant proportion of the children walk to school because they have no other option for transportation. Therefore, our results could be used to classify countries into four typologies that could be useful for future AST interventions ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Specifically, in LMIC where car availability remains relatively low in comparison with HIC, AST may be more reflective of need rather than choice since a significant proportion of the children walk to school because they have no other option for transportation. Therefore, our results could be used to classify countries into four typologies that could be useful for future AST interventions ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Multicountry studies have shown similar proportions of active transportation involvement in significantly differing contexts. 89,90 To understand these patterns a "need-based framework" has been proposed for LMIC, where active transportation represents the only option for transportation because motorized vehicle availability remains relatively low in comparison with HIC. The patterns observed in HIC can be understood within a "choice-based framework" where policies and infrastructure facilitate active transportation as an option to commute.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
“…Cuernavaca, an urban setting with a population of 365,168 inhabitants located 76 km south of Mexico City, has a similar prevalence of overweight and obesity compared to the whole country, 3 and can be considered a standard Mexican city in size and structure. 25,26 Additionally, Cuernavaca is home to the headquarters of the Mexican National Public Health Institute (Instituto Nacional de Salud Pública, INSP). Moreover, Cuernavaca served as the Mexican site for the International Physical Activity Environment Network (IPEN) Adult Study.…”
Section: Study Sitementioning
confidence: 99%
“…For IPEN-Mexico, Cuernavaca census tracts were stratified according to socioeconomic status (SES) (median split: high/low) and walkability (median split: high/low) and eight census tracts were randomly selected per SES/walkability stratum. 25,26 The walkability index was calculated using z-scores of intersection density (number of 4-way intersections over total area per census tract), land use mix (diversity of land use types per census tract, using a normalized entropy score ranging from 0 to 1), 28 proportion of commercial land use (over total census tract area), and net residential density (total residences over area destined for residential use per census tract). 27 We selected one neighborhood from each stratum (low SES/ high walkability; low SES/low walkability; high SES/high walkability; high SES/low walkability) to examine the acceptability and feasibility of the Nuestra Voz approach to measuring and potentially modifying local neighborhood environments in distinct types of Mexican neighborhoods.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation